Análisis bibliométrico de los trabajos de grado del área organizacional de la Facultad de Psicología de la Universidad Santo Tomás (2007)
The aim of this research was to make a bibliometric analysis of the works of works of degree into the organizational area in the faculty of psychology at the Santo Tomas University. First, a general overhaul of the works of degree of Psychology was made (1307 theses) of which were selected 247 of the organizational area produced during 26 years (close to the 19%) of history of the Faculty - period between 1985-2005-. Then, a data base was designed and in agreement with the variables previously established (author, year, thematic, director, juries, approach, methodology, design, type of statistical analysis and references) the data were systematized. This study was a descriptive one and tow types of analysis were made, one is a bibliometric descriptive and the second, corresponds to the analysis of textual data. It was find that into the 247 works revised, in 1995 were the year in which more number of thesis were developed (50 works): the theorist perspectives more used in that works were: systemic (51 works), followed by cognitive-behaviorist (26). Finally, a worth methodology contribution is presented, and it is the inclusion of the textual data analysis in the bibliometric study, which revels the relation between Social and Organizational Psychology. In a second place, it was evident two periods: one characterized by a classic vision of organizational psychology, and other, in the last 10 years, whit an emphasis in a psychological critical perspective in the organizations. Key words: Bibliometric analysis, analysis of textual data, work and organizations psychology.